Plastic industry waste and air pollution: “Environmental and health impacts and future effects” -Algrapolly area as a model (The International Journal for Scientific Research, 2024)
The research dealt with the grapolly area and the plastic waste it suffers from, the study dealt with the definition of plastic waste, its types and methods of disposal and the research in his study relied on two descriptive and analytical approaches, this is in addition to reviewing the objectives and importance of research to create an environment suitable for all organisms in addition to some strategic plans to reduce plastic waste and clarify its impact on the surrounding environment, besides studying the future of plastic industries and reaching the results and recommendations that I hope to take into account in the future.
Keywords: Waste; Plastic; Polymer; Pollster; Polluion